(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
The Unconfined Compressive Strength (UCS) test is one of the most common methods for determining the rock material strength value. However, the size and complexity of the instrument do not allow UCS testing to be carried out in the field. The UCS value can be estimated in the field by converting the rebound number using the Schmidt hammer test. This research aims to carry out a comparative analysis and evaluation of the conversion formula for rock compressive strength values resulting from the Schmidt hammer test and UCS test in a case study of andesite rock slopes at Graha Puspa, Lembang Fault, Bandung, Indonesia. Rock hardness testing was carried out using the Schmidt hammer test on five segments at Graha Puspa. UCS testing was carried out using a compressive strength machine on four samples in Graha Puspa. The test results show a rebound number value ranging from 31.67 - 45, while the UCS test results show a value range of 134.96 – 171.60 MPa The results of the previously published empirical equations differed considerably from the results of the UCS tests on rock samples in the laboratory when estimating the UCS values. From this evaluation, this research proposed formulation development of andesite rock formulation in the Lembang Fault area. However, UCS testing on more samples is highly recommended in order to obtain a compressive strength conversion formula that is more suitable for the case study at this location.